Assessing the impact of a waste incinerator on the environment using the MAIAC-AOD and AERMOD models - Hongthong, Anuttara; Nakapan, Supachai (Frontiers in Environmental Science, 2023)
The distribution and concentration of air pollutants from infectious waste incineration between 2019 and 2021 were examined in this study using an AERMOD model, including sulfur dioxide (SO2), nitrogen dioxide (NOx), and particulate matter (PM2.5). The MAIAC-AOD value at a 1 km resolution was used to develop a regression model with meteorological information for predicting PM2.5, which was then compared with the concentration from the AERMOD simulation. The following maximum 1-h, 24-h, and annual average concentrations of all pollutants were found to have occurred in 2019. The distribution of SO2 and NOx in 1 h was largest in 2020 at 1,000 m to the northwest, with concentrations of 37.68 and 93.99 μg/m3, respectively. The 24-h concentrations of SO2 and NOx were greatest in 2021 at 3.63 and 8.90 μg/m3, respectively, 720 m northeast of the stack. The annual concentrations of SO2 and NOx were highest in 2019 at 0.56 and 1.36 μg/m3, respectively. The highest annual PM2.5 concentration was 0.033 μg/m3, 730 m to the northeast in 2019. The predicted PM2.5 using MAIAC-AOD correlated with the simulated value from AERMOD, with R2 values of 0.7630, 0.7607, and 0.6504 for 2019, 2020, and 2021, respectively, which were higher closer to the stack than outside. As a result, investigations into the distribution of air pollution should benefit from the integration of air modeling and satellite information.